INFLUENCE OF VEGETATION DISTRIBUTION ON SEDIMENT YIELD IN FORESTED MARLY GULLIES - Rey F. (My University, 2003)
The cover provided by forest vegetation makes it possible to fight erosion efficiently. Furthermore, vegetation barriers can also play a major role by trapping eroded sediments and thus vegetation located downslope of a gully can be important. The objective of this study is to highlight the role of vegetation distribution in a marly gully in reducing sediment loss at the outlet. To do this, sediment yield in gullies with similar geological and geomorphological components, but with different vegetation cover and distribution, was studied for 2 years. Sediment traps installed at gully outlets permitted the distinction of active gullies from inactive ones. The results show that gully activity is not correlated with the percentage of total vegetation cover, but with the percentage of cover of low vegetation in the gully floor. This is due to sediment trapping processes and highlights the importance of the spatial distribution of forest vegetation in reducing sediment yield at the gully outlet. Thus, gullies with similar total vegetation cover can have very different activities, and inactive gullies exist that are only partially covered with vegetation. Inactive gullies with as low as 33% vegetation cover occur where vegetation is mainly present in the gully floor. The results also show that above 50% cover of low vegetation in the gully floor as a percentage of the gully floor surface, gullies are generally inactive.
Keywords: EROSION; MARLS; GULLY; FOREST VEGETATION; VEGETATION DISTRIBUTION; SEDIMENT TRAPPING